A Bio-inspired Coverage and Connectivity Maintenance Algorithm - Mathews, Emi; Graf, Tobias; Kulathunga, K. S. S. B. (Sixth International ICST Conference on Bio-Inspired Models of Network, Information, and Computing Systems)

Aspect enhanced functional coverage driven verification in the SystemC HDVL - Kuznik, Christoph; Müller, Wolfgang (Proc. of the 8th International SoC Design Conference 2011 (ISOCC 2011))

IP-XACT based System Level Mutation Testing - Xie, Tao; Müller, Wolfgang (Proceedings of the 16th IEEE International High Level Design Validation and Test Workshop (HLDVT))

Model-driven runtime resource predictions for advanced mechatronic systems with dynamic data structures - Henkler, Stefan; Oberthür, Simon; Giese, Holger; Seibel, Andreas (International Journal of Computer Systems Science & Engineering 26 (6))

Enabling Constraint-based Binary Reconfiguration by Binary Analysis - Baldin, Daniel; Grösbrink, Stefan; Oberthür, Simon (International Journal on Computing (JoC) 1(4))

F-DRARE: A Framework for Deterministic runtime adaptation of Cyber Physical Systems - Bin Tariq, Fahad (1st International Workshop on Adaptive Services for the Future Internet, 4th European Conference, ServiceWave 2011)

High-Level Construction of Emergent Self-Organizing Behavior in Massively Distributed Embedded Systems - Orfanus, Dalimir; Janacik, Peter; Eliassen, Frank; Orten, Pal (Proceedings of Third World Congress on Nature and Biologically Inspired Computing (NaBIC2011))

Ausgewählte Probleme des Logistikmanagements

HDL-Mutation Based Simulation Data Generation by Propagation Guided Search - Xie, Tao; Müller, Wolfgang (Proceedings of the 14th Euromicro Conference on Digital System Design (DSD))

A Test Bed for Investigating Self-X Properties in Multi-Robot Societies - Jungmann, Alexander; Lutterbeck, Jan; Werdehausen, Benjamin; Kleinjohann, Bernd (Proceedings of the 9th IEEE International Conference on Industrial Informatics (INDIN))
In this paper, we introduce a test bed for demonstrating and investigating self-x properties, such as self-optimization and self-organization, within the scope of multi-robot societies under realistic conditions. By doing so, we shift the investigation and demonstration of biologically inspired mechanisms from the simulative point of view to a dynamic and more complex realistic environment. For this purpose, we developed a controlled real-world environment to overcome common problems such as self-localization. Furthermore, we elaborated a concept for a descriptive robotic real-world game. By means of this game, we provide an instrument, which is easily accessible for any kind of audience on the one hand, while it still leaves enough space for an extensive scientific investigation on the other hand.

Miniature Robot BeBot: Mechatronic Test Platform for Self-X Properties - Gausemeier, Jürgen; Schierbaum, Thomas; Dumitrescu, Roman; Herbrechtsmeier, Stefan; Jungmann, Alexander (Proceedings of the 9th IEEE International Conference on Industrial Informatics (INDIN))
Machines are omnipresent. They produce, they transport. Machines facilitate work and assist. The increasing penetration of mechanical engineering by information technology enables considerable benefits. We refer to such systems as advanced mechatronic systems, which relay on the close interaction of mechanics, electric/electronics, control engineering and software engineering. Hence, the design and production of such systems is an interdisciplinary and complex task. Our ambition is a new school for the design of advanced mechatronic systems. Consequently, we need an avant-garde basic system which can be used to develop and to test future applications. The miniature robot BeBot is such a basic system. This robot constitutes the test bench for the applications, being based on modern approaches, such as self-optimization, self-organization and self-coordination as well as on the use of new manufacturing technologies.

Comparison of periodic and aperiodic task models for cyber-physical-systems - Thuy, Andreas (Reconfigurable Communication-centric Systems-on-Chip (ReCoSoC), 2011 6th International Workshop on)

Verification Closure of SystemC Designs with Functional Coverage - Kuznik, Christoph; Müller, Wolfgang (North American SystemC User Group Meeting (16th))
In the area of dynamic verification of virtual prototypes, functional coverage is a valuable tool for answering the "Are we done?" question and achieving verification closure. Recent verification methodologies such as OVM and UVM contain multi-language support that provides a basic SystemC version. However, due to language shortcoming they cannot be utilized for the same amount of verification tasks in the SystemC ecosystem as in other supported hardware design and verification languages. In this presentation, we propose to boost the verification capabilities of SystemC by implementing functional coverage collection and evaluation according to the same metric as defined in the widely accepted IEEE-1800 SystemVerilog cover group feature. We implement a functional coverage library to enable coverage-driven verification of SystemC designs on multiple levels of abstraction enabling value, transition, and expression coverage. To our knowledge, the overall functionalities are not available in the IEEE-1666 SystemC standard or the SCV add-on library, nor are they complete compared to the aforementioned in any publicly available SystemC library.

A Localized Planarization Algorithm for Realistic Wireless Networks - Mathews, Emi; Frey, Hannes (IEEE International Symposium on a World of Wireless, Mobile and Multimedia Networks (WoWMoM))
Planar graph routing works provably correct if the underlying network graph is connected and planar. Typically, wireless networks modeled as 2D graphs, are not planar and planar graph routing applied on such unprocessed network graphs may fail. Planarizing a given connected graph by removing intersecting links might be impossible if the outcome still needs to be a connected subgraph. It becomes even more difficult with distributed planarization techniques, where each node is allowed to use only the information about its local neighborhood. Furthermore, it is getting complicated if the nodes' assigned positions do not reflect the exact physical location. With or without exact location information, the outcome might be disconnected, nonplanar, or both of it. With all these unsolvable problems, the question arises how to apply planar graph routing in a realistic network setting? Fortunately, wireless network graphs bear one property which distinguishes them from arbitrary graphs: due to limited communication range, network links cannot become arbitrarily long. In this work we exploit this locality property to build a new localized planarization algorithm, which is location fault tolerant and which produces planar connected graphs in most cases in realistic wireless models. We evaluate our algorithm using the Log Normal Shadowing model and show that our algorithm always produces planar connected graphs in all simulations even when large location errors are present.

Virtual Prototyping softwareintensiver mechatronischer Systeme Eine Fallstudie - Becker, Markus; Zabel, Henning; Müller, Wolfgang; Elfeky, Ahmed; DiPasquale, Anthony (8. Paderborner Workshop Entwurf mechatronischer Systeme, Band 294)

Coordinated Exploration and Goal-Oriented Path Planning using Multiple UAVs - Rasche, Christoph; Stern, Claudius; Kleinjohann, Lisa; Kleinjohann, Bernd (ThinkMind, International Journal On Advances in Software 3 (3&4))

Self-Organized Cooperation in Swarm Robotics - Khaluf, Yara; Mathews, Emi; Rammig, Franz-Josef (14th IEEE International Symposium on Object/Component/Service-Oriented Real-Time Distributed Computing Workshops (ISORCW))

A Reconfiguration Approach for Fault-Tolerant FlexRay Networks - Klobedanz, Kay; König, A.; Müller, Wolfgang (Proceedings of Design, Automation, Test Europe - DATE2011)

Self-Reconfiguration for Fault-Tolerant FlexRay Networks - Klobedanz, Kay; König, A.; Müller, Wolfgang; Rettberg, Achim (Second IEEE Workshop on Self-Organizing Real-Time Systems - SORT 2011)

Functional Coverage-driven Verification with SystemC on Multiple Level of Abstraction - Kuznik, Christoph; Müller, Wolfgang (Proceedings of DVCON)
SystemC is a versatile C++ based design and verification language, offering various mechanisms and constructs required for embedded systems modeling. Using the add-on SystemC Verification Library (SCV) elemental constrained-random stimuli techniques may be used for verification. However, SCV has several drawbacks such as lack of a functional coverage facility supporting coverage collection on RTL and TLM models. In this article we present a functional coverage library which implements parts of the IEEE 1800-2005 SystemVerilog standard capturing functional coverage throughout the design and verification process, and allows to facilitate coverage-driven verification in SystemC.